The case for grace : a journalist explores the evidence of transformed lives - Strobel, Lee, 1952- (Grand Rapids, Michigan : Zondervan : Willow Creek Resources, 2015)
"Lee draws upon his own journey from atheism to Christianity to explore the depth and breadth of God's redeeming love for spiritually wayward people. He travels thousands of miles to capture the inspiring stories of everyday people whose values have been radically changed and who have discovered the how and why behind God's amazing grace"--Amazon.com.
The search for grace -- The mistake -- The orphan -- The addict -- The professor -- The executioner -- The homeless -- The pastor -- The prodigal -- Empty hands -- Grace withheld, grace extended -- Appendix. What the bible says about grace.
Includes bibliographical references.
Keywords: Grace (Theology); Christian life; Christian life; Grace (Theology.); Christian life